Generation of Mitochondria-Depleted (Rho0) MDA-MB-231 Cells and Characterization. - Kenzhetay, B.; Dildabek, A.; Burska, A.N. (Eurasian Journal of Applied Biotechnology, 2025)
Mitochondrial depletion models are indispensable for understanding the role of mitochondrial function in cancer metabolism and signaling. However, traditional approaches such as ethidium bromide or nucleoside analogue treatments often induce nuclear mutagenesis and incomplete mitochondrial clearance. Here, we present a controlled and reproducible strategy to generate mitochondria-depleted (Rho0) MDA-MB-231 breast cancer cells through enforced mitophagy driven by Parkin overexpression. Stable Parkin-overexpressing (PKN OE) cells were established via lentiviral transduction and subjected to repetitive mitochondrial depolarization using carbonyl cyanide m-chlorophenyl hydrazone (CCCP) in uridine- and pyruvate-supplemented medium. This approach triggered sustained PINK1–Parkin pathway activation, resulting in progressive mitochondrial clearance. Quantitative PCR confirmed >95% reduction in mitochondrial DNA (ND1) copy number, while immunoblotting showed loss of TOMM20 and VDAC1. Confocal microscopy with MitoTracker Deep Red revealed a near-complete absence of the mitochondrial network. Despite mitochondrial depletion, cells maintained viability and displayed metabolic adaptation, with no significant change in basal ATP or lactate levels. Cell proliferation and cell cycle analyses demonstrated slower growth and G1 accumulation in Rho0 cells, reflecting impaired bioenergetic support for DNA synthesis. This Parkin-mediated mitophagy model provides a physiologically relevant and non-mutagenic platform for studying mitochondrial dysfunction, metabolic plasticity, and retrograde signaling in triple-negative breast cancer. It offers a versatile tool for future investigations into therapeutic resistance, mitochondrial translation disorders, and mitochondrial-nuclear communication in tumor progression.